Sistemas agroflorestais e resiliência socioecológica da agricultura familiar na Amazônia Mato-grossense - Lopes, Jessica Helena Christofoletti (2025)
Socio-Ecological System (SES) is a term that reflects the complexity inherent in human-nature relationships. Assessing the resilience of these systems—generally understood as their capacity to adapt to shocks—is of critical importance within the context of Family Farming (FF), given the range of economic, social, and environmental challenges this sector continuously faces. The use of Agroforestry Systems (AFS) can provide several benefits in response to these challenges, such as increased agrobiodiversity, support in coping with climate change, improved soil conditions, income generation, and food sovereignty in rural communities, among others. One of the most recent shocks experienced by family farming was the Covid-19 pandemic, which brought new challenges and required adaptive responses within this SES. In this context, studies are needed to understand how AFS can serve as a strategy for increasing and/or strengthening resilience in the socio-ecological systems of family farming across different localities and cultural, socioeconomic, and environmental contexts. This research was conducted in the Portal da Amazônia Territory (TPA) in northern Mato Grosso, involving rural communities that implemented AFS aimed at forest restoration (in Permanent Preservation Areas and Legal Reserves) and food production (in agroforestry orchards). The study is organized into two chapters: the first presents the theoretical framework, and the second analyzes AFS as a factor of resilience for family farmers in the study area in response to the Covid-19 shock. To this end, semi-structured interviews with local family farmers and content analysis were employed. The findings indicate that the implemented AFS contributed to food security among the participants, and that alternative marketing strategies played a key role in strengthening family farming, in addition to providing environmental benefits for the region.